1994
DOI: 10.1016/0014-5793(94)00795-0
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian 3,β‐hydroxysteroid dehydrogenase/Δ5‐4‐isomerase of rainbow trout: Its cDNA cloning and properties of the enzyme expressed in a mammalian cell

Abstract: A cDNA clone encoding 3j%hydroxysteroid dehydrogenaseld S4-isomerase (3j%HSD) was isolated from a cDNA library of rainbow trout ovarian thecal cells. Southern hyb~dization analysis of trout genomic DNA with the cDNA suggested the presence of a single gene encoding 3&HSD in the rainboa trout showing a total genomic size of less than 4 kilobases (kb). The cDNA hybridized to a single species of mRNA isolated from rainbow trout ovaries; the 1.4 kb transcripts were most abundant m trout ovaries during the later sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Unchanged abundance of 3β‐HSD transcripts during oocyte growth and maturation does not coincide with observations on rainbow trout Oncorhynchus mykiss. 13 In rainbow trout, 3β‐HSD mRNA levels increased at the LV stage to facilitate the production of maturation‐inducing steroids 13 . This difference suggests that in Japanese eel, absence of expressional changes in 3β‐HSD, which converts Δ5 steroids to Δ4 steroids, does not confound the production of sex steroids such as T. In contrast, the mRNA levels of P450scc, P450c17 and 17β‐HSD‐I increased as eel ovarian development proceeded.…”
Section: Discussionmentioning
confidence: 99%
“…Unchanged abundance of 3β‐HSD transcripts during oocyte growth and maturation does not coincide with observations on rainbow trout Oncorhynchus mykiss. 13 In rainbow trout, 3β‐HSD mRNA levels increased at the LV stage to facilitate the production of maturation‐inducing steroids 13 . This difference suggests that in Japanese eel, absence of expressional changes in 3β‐HSD, which converts Δ5 steroids to Δ4 steroids, does not confound the production of sex steroids such as T. In contrast, the mRNA levels of P450scc, P450c17 and 17β‐HSD‐I increased as eel ovarian development proceeded.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent BLAST database search (Altshul et al 1997) did not find any proteins with at least 35% sequence identity to 3 / 5-4 -HSD in D. melanogaster, C. elegans or any other invertebrate (not shown). 3 / 5-4 -HSD is found in mammals and trout (Sakai et al 1994). Sequences with over 40% identity to a known 3 / 5-4 -HSD are found in cartilaginous fish.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonids are excellent study animals to examine the changes in steroidogenic enzyme gene expression in relation to steroid hormone synthesis, since germ cell development progresses in a synchronous fashion and dynamic changes in steroid hormone secretion occur during gametogenesis. In rainbow trout, cDNAs for most of the steroidogenic enzymes responsible for the synthesis of sex steroids have already been isolated: cytochrome P450 cholesterol side-chain cleavage (P450scc) (Takahashi et al 1993), cytochrome P450 17 -hydroxylase/17,20-lyase (P450C17) (Sakai et al 1992), 3 -hydroxysteroid dehydrogenase/n5-4-isomerase (3 -HSD) (Sakai et al 1994), cytochrome P450 aromatase (P450 arom) , cytochrome P450 11 -hydroxylase (P45011 ) (Liu et al 2000, Kusakabe et al 2002a, 11 -hydroxysteroid dehydrogenase (11 -HSD) (Kusakabe et al 2003) and 20 -hydroxysteroid dehydrogenase (20 -HSD) (Guan et al 1999). Recent studies reported changes in mRNA levels for key ovarian steroidogenic enzymes during a reproductive cycle in channel catfish (Kumar et al 2000), Arctic char (von Hofsten et al 2002) and rainbow trout (Nakamura et al 2005), and a few recent studies in male teleosts reported seasonal changes in transcript levels of a single steroidogenic enzyme (Liu et al 2000, Kusakabe et al 2002a.…”
Section: Introductionmentioning
confidence: 99%